The Queuing System Analysis for Patient Registration Counters at a Hospital - Ramadhan, Ferdinan; Vikaliana, Resista (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
Hospitals are vital for healthcare and must continually enhance service quality to boost patient satisfaction. Lengthy outpatient service times, particularly during peak demand, can detrimentally affect service quality. This study investigates the application of queuing theory to the registration service facilities at PKK Hospital. The goal is to identify an appropriate queuing model to describe the outpatient registration counters' conditions and assess the model's performance. The research employs a quantitative approach, using data from observations and literature review, with purposive sampling. The study concludes that the Multiple Channel – Single Phase queuing model is most suitable for describing the outpatient registration counters at PKK Hospital. According to the findings, this queuing model offers optimal performance, with an average service time of 4.076 minutes per patient and a corresponding waiting time of approximately 3-8 minutes.